Vulnerability Life of LGBT Community in Curup Rejang Lebong Regency of Bengkulu Province - Yessilia Osira; Bayu Risdiyanto; Nugroho Iskandar (Asian Social Work Journal, 2017)
Lesbian, Gay, Bisexual, and Transgender, or we known as LGBT is one of community that has vulnerability life. This research indicates that besides interacting and experiencing various disorders in social intersection aspects with family and society, healthy, education and work aspects, actually the LGBT’s community also has adaptation ability even utilizing to increase their well-being. Base on that, should be made social protection efforts through various activities of capacity building and social advocacy for LGBT’s community in facing their vulnerability.